Population Dynamics of Insect Pests of Psoralea Corylifolia - Kumar, Arvind (Indian Forester, 2014)
The field experiment was carried out during Kharif season to investigate the population dynamics of insect pest th th associated with Psoralea corylifolia (Babchi). Six insect pests viz. Papilio demoleus from 14 August to 27 of st th nd th November, Aproaerema modicella from 31 July to 27 of November, Helicoverpa armigera from 2 of October to 27 th th th th of November, Tricentrus bicolor from 11 of September to 20 November, Haltica sp. 14 of August to 9 October and th th Kollasp observed from 28 of August to 13 of November infesting to Babchi